2014
DOI: 10.1212/wnl.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Taurine trial in succinic semialdehyde dehydrogenase deficiency and elevated CNS GABA

Abstract: Objectives: The objective of this open-label study was primarily to assess the effect of taurine on adaptive behavior and secondarily to collect safety and tolerability data in patients with succinic semialdehyde dehydrogenase deficiency.Methods: In the current study, subjects were titrated weekly from a starting dose of 50 mg/kg/d to a target 200 mg/kg/d, and assessed for safety, tolerability, and adaptive functioning using agenormalized Adaptive Behavior Assessment Scales.Results: Eighteen patients (8 males/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…However, a borderline lower score was observed on the conceptual (p=0.1) index during taurine use. Our open-label pilot trial of taurine in patients with SSADH deficiency did not reveal demonstrable improvement in adaptive neurobehavioral functioning (Pearl et al 2012). Nonetheless, additional biomarker studies during taurine intervention are in progress.…”
Section: Treatment Strategies For Ssadh Deficiencymentioning
confidence: 74%
“…However, a borderline lower score was observed on the conceptual (p=0.1) index during taurine use. Our open-label pilot trial of taurine in patients with SSADH deficiency did not reveal demonstrable improvement in adaptive neurobehavioral functioning (Pearl et al 2012). Nonetheless, additional biomarker studies during taurine intervention are in progress.…”
Section: Treatment Strategies For Ssadh Deficiencymentioning
confidence: 74%
“…Early reports of uncontrolled trials suggested a potential benefit of taurine intervention in patients (Saronwala et al 2008), although we were unable to document significant changes using an adaptive behavior scale in an open-label study (Pearl et al 2014). Here, we report the effects of taurine on TMS measures of cortical excitability and inhibition, CSF biomarkers, and cognitive testing in a group of these patients participating in the open-label taurine trial.…”
mentioning
confidence: 68%
“…One subject was already taking taurine and completed the "on" assessment first. All subjects were titrated to 10 g daily, the maximum dose based on hypersomnolence noted on higher doses as reported in the open-label trial (Pearl et al 2014). No adverse events were reported during TMS.…”
Section: Resultsmentioning
confidence: 99%
“…Further, long-term treatment with VGB is contraindicated due to marked and permanent visual-field impairments (Singh et al 2013; Froger et al 2014; Good et al 2011; Pellock 2011; Escalera et al 2010; Casarano et al 2011; Matern et al 1996; Al-Essa et al 2000). Of further concern is the predicted expectation that VGB will augment brain GABA (Ergezinger et al 2003; Pearl et al 2014a; 2014b), which is a relevant observation in light of recent studies (described above) highlighting GABA-induced impairment of autophagic processes (Vogel et al 2015). The potential use of mTOR inhibitors (e.g., rapamycin, Torin 1 or 2) along with VGB might be an effective intervention, since this would both decrease production of GHB and clear the oxidative-damaging effects of further-enhanced GABA levels.…”
Section: Treatment Of Ssadhdmentioning
confidence: 99%